Understanding the connection and relation between sleep and depression in a tertiary health-care center: Insights from a cross-sectional study - M. Aravindh; Kailash Sureshkumar; Shabeeba Z. Kailash; P. R. Sobia; V. Madhumitha (Archives of Mental Health)
Background: There is a bidirectional relationship between sleep disturbance and depression, with which a new hypothesis could be generated, that is, sleep disturbance can be a prodromal event rather than a symptom of depression. Many long-term studies have identified insomnia as a risk factor for the onset or recurrence of depression in young, middle-aged, and older people and it can also increase the risk of self-harm and suicide, which can also exacerbate the medical comorbidity conditions and also increase the substance intake. Materials and Methods: Those patients attending the psychiatry outpatient department of tertiary Health-care center for 6 months were considered. Those patients who were diagnosed with depression as per the International Classification of Diseases-11 depression criteria were taken after getting proper informed consent from them. Then, those patients who satisfied the inclusion criteria were taken into the study and evaluated with self-structured pro forma including details regarding the sociodemographic profile, Hamilton Depression Rating Scale, and Insomnia Severity Index Scale to assess the severity of depression and sleep disturbance. Results: The prevalence of sleep disturbance in depressive individuals was found to be 78% (140). The significance was established between the severity of depression and the severity of insomnia (P<0.001), along with sleep duration (P<0.001), insomnia type (P=0.002), benzodiazepine usage (P<0.001) and self-harm ideas/attempts (P<0.001). Conclusion: Sleep is considered a major aspect of holistic care, as it may have an impact on the severity, frequency and duration of depression and its remission along with quality of life and mortality rate.